Gennaro to retire after 29 years (Albuquerque Journal Albuquerque, New Mexico, 1976)
Newspaper Article on Nash Gennaro's retirement as teacher after 29 years.
Master list item #: 26
File location is in the Raton File Cabinet
Keywords: Gennaro, Nash; Columbian School; Bernal School; Longfellow School; University of Illinois; Local History; Biography; Life and Customs; Teacher; Education; Retirement; Raton, New Mexico; Maxwell, New Mexico; Colfax County